2021
DOI: 10.38037/jsm.v15i1.178
|View full text |Cite
|
Sign up to set email alerts
|

Perilaku Merokok di Masa Covid-19

Abstract: Jumlah perokok di Indonesia cenderung bertambah yaitu 31,5% dari penduduk Indonesia tahun 2001, bahkan lebih dari 50 % dengan sampel di suatu daerah, dan semakin dini segi usia memulai merokok. Menurut kemenkes, 2020 Perokok lebih mungkin terjangkit COVID-19 dibandingkan dengan orang yang tidak merokok.  Penelitian ini bertujuan untuk Untuk mengetahui Perilaku Merokok di Masa Pandemi COVID-19. Jenis penelitian yang dilakukan adalah Jenis penelitian yang digunakan adalah penelitian kuantitatif  Deskriptif. popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Data provided by WHO in 2018 (WHO, 2019) and Riskesdas in 2018 (Kementrian RI, 2018) revealed that 70.7% and 62.9% of males in Indonesia were active smokers. The nicotine concentration in cigarettes activates ACE-2 receptors on the lung's respiratory epithelium and endothelial cells, thereby increasing access to SARS-CoV-2 and making it bind to the receptors (Ruhyat, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Data provided by WHO in 2018 (WHO, 2019) and Riskesdas in 2018 (Kementrian RI, 2018) revealed that 70.7% and 62.9% of males in Indonesia were active smokers. The nicotine concentration in cigarettes activates ACE-2 receptors on the lung's respiratory epithelium and endothelial cells, thereby increasing access to SARS-CoV-2 and making it bind to the receptors (Ruhyat, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Pengaktifan reseptor ACE2 ini akan memfasilitasi SARS-CoV-2 untuk masuk dan berikatan dengan reseptor ACE2 pada sel epitel dan endotel saluran pernapasan. Hal inilah yang mengakibatkan laki-laki yang merokok lebih rentan terinfeksi COVID-19 dibandingkan perempuan yang tidak merokok (Ruhyat, 2021). Merokok juga dapat menyebabkan keadaan prokoagulan, peradangan, peningkatan kadar fibrinogen plasma, peningkatan faktor VIII, berkurang proses fibrinolisis dan peningkatan kekentalan darah yang dapat berkembang menjadi VTE (Tromboemboli Vena).…”
Section: Rsud Dr M Yunusunclassified
“…During lockdown restrictions, nicotine use increased in five countries: Italy, India, South Africa, the United States, and the United Kingdom, including Indonesia (Ruhyat, 2021;Yach, 2020). Indonesia remains the first country for male smokers globally (Holipah et al, 2020).…”
Section: Introductionmentioning
confidence: 99%